2014
DOI: 10.1111/jfb.12261
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of novel thrombocytes in the dog snapper Lutjanus jocu

Abstract: Myxosporean cysts containing spores of Henneguya sp. were observed in the gills of the dog snapper Lutjanus jocu. Adjacent to the cysts were capillaries, allowing observation of peripheral blood cells. Numerous white blood cells displaying uncommon cytoplasmic projections were observed amongst the erythrocytes. Their morphology allowed them to be identified as thrombocytes (TCs). Each TC displayed 18-26 cytoplasmic projections, most of which were in close proximity to erythrocytes. At their apical end, each cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Nonetheless, our observations seem to be the first study reporting the natural occurrence of EAg in fish infected by a myxosporean species. Despite the many studies reporting parasitosis in myxosporean species in other Brazilian fish hosts (Azevedo et al, 2014;Casal et al, 2019;Eiras & Adriano, 2012;Mathews et al, 2016;Rocha et al, 2014), none of these have reported the occurrence of hemagglutination, as a consequence of infection. Moreover, several of the abovementioned studies used LM and molecular procedures and may have missed changes that are only detectable via TEM.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our observations seem to be the first study reporting the natural occurrence of EAg in fish infected by a myxosporean species. Despite the many studies reporting parasitosis in myxosporean species in other Brazilian fish hosts (Azevedo et al, 2014;Casal et al, 2019;Eiras & Adriano, 2012;Mathews et al, 2016;Rocha et al, 2014), none of these have reported the occurrence of hemagglutination, as a consequence of infection. Moreover, several of the abovementioned studies used LM and molecular procedures and may have missed changes that are only detectable via TEM.…”
Section: Discussionmentioning
confidence: 99%
“…300 Azevedo et al ( 2014) found that thrombocytes of dog snapper (Lutjanus jocu) surrounded by red blood cells could form multiple cytoplasmic processes and present irregular cell membranes, and thrombocytes approached the cell membranes of multiple red blood cells by projection. 301 The heterochromatin and euchromatin in the nucleus of thrombocytes contain some granular fibrils and some developing vacuoles, and some of these vacuoles are located at the tip of cytoplasmic processes, and some are randomly distributed in the cytoplasm. Recent studies have shown that the cell membrane of human platelets has pseudopodia and protrusions, and the cell interior has vacuoles, α-granules, dense granules and lysosomal granules, tubular system, mitochondria and autophagosomes.…”
Section: Role Of Leukocyte Parameters In Healthy Fish Culturementioning
confidence: 99%
“…The thrombocytes of Centropomus parallelus are spindle‐shaped and globular, with central euchromatin in the nucleus and vacuoles, tubular systems and phagosomes in the cytoplasm 300 . Azevedo et al (2014) found that thrombocytes of dog snapper ( Lutjanus jocu ) surrounded by red blood cells could form multiple cytoplasmic processes and present irregular cell membranes, and thrombocytes approached the cell membranes of multiple red blood cells by projection 301 . The heterochromatin and euchromatin in the nucleus of thrombocytes contain some granular fibrils and some developing vacuoles, and some of these vacuoles are located at the tip of cytoplasmic processes, and some are randomly distributed in the cytoplasm.…”
Section: Blood Physiological Indexmentioning
confidence: 99%